Efeitos do campo magnético sobre processos de corrosão em aço AISI 1020 - Oliveira, Aloadir Lucas Santos de (Universidade Federal de São Carlos, 2017)
In this dissertation the effects of the application of magnetic field during the electrochemical reactions of corrosion in samples of steel AISI 1020 in KNO_3 solution were investigated. The experiments were measurements of open circuit potential and linear scanning voltammetries, with and without magnetic field applied. After each experiment, optical microscopy images of the surfaces of the electrodes ware taken. Computational simulations of the magnetic and electric fields were performed around a steel sample with the purpose of simulating the experimental conditions. The results showed, at the same time, the magnetic field, there was modification of the corrosion potential to more positive values. In addition, as electrode images show that in the condition of magnetic field applied there were changes in the formation of oxide film due to corrosion, when compared to the situation without applied magnetic field. The computational simulations showed that the magnetic and electric fields generate a Lorentz force around the steel sample with different divisions on either side of the flat surface of the disk. This asymmetry may explain the morphology of the oxide film grown due to corrosion.
Effects of the magnetic field on corrosion processes in steel AISI 1020
Keywords: Corrosão; Campo magnético; Força de Lorentz; Comsol; Corrosion; Magnetic field; Lorentz force; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA::MATERIAIS MAGNETICOS E PROPRIEDADES MAGNETICAS